New opportunities for EU-China-Africa trilateral cooperation on combatting climate change - Alexander Demissie; Moritz Weigel (Deutsches Institut für Entwicklungspolitik (DIE), 2017)
The entry into force of the Paris Agreement under the United Nations Framework Convention on Climate Change (UNFCCC) on 4 November 2016 is a milestone towards safeguarding an opportunity for our species to live in peace and dignity on this planet. It is the first universal, legally binding instrument requiring both developed and developing countries to tackle climate change as a joint responsibility. While developed countries reconfirmed their obligation to provide support to developing countries under the Paris Agreement, there is also a growing recognition of the importance and potential of new partnerships among and with developing countries through South-South and trilateral cooperation. The European Union (EU), having shown considerable leadership in forging the Paris Agreement, also expressed its intent to work trilaterally with China and African countries to support the treaty's implementation. The new EU strategy on China proposes to turn what is often perceived as EU-China competition in Africa into “greater cooperation” and to pursue “joint approaches” to “speed up the implementation of the Paris Agreement wherever possible, including the implementation of Nationally Determined Contributions” (European Commission, 2016). Cooperation on addressing climate change has been part of China's Africa policy since 2006, and China has been increasingly supporting African countries through South-South cooperation as well as trilateral cooperation with the involvement of United Nations entities. In 2015, China committed to significantly scaling-up its efforts in the area by pledging 20 billion Chinese yuan (CNY) (USD 3.1 billion) to its recently established South-South Cooperation Climate Fund, which will focus on supporting African countries. Trilateral cooperation between the EU, China and African countries should be guided by Africa's priorities. There are 53 African countries that have communicated their national plans on addressing climate change under the Paris Agreement through the submission of so-called (Intended) Nationally Determined Contributions ((I)NDCs). Based on an analysis of (I)NDCs and a review of existing partnerships and recent pan-African developments, this briefing paper proposes for EU-China-Africa trilateral cooperation to initially focus on renewable energy. The African Union's newly launched Africa Renewable Energy Initiative (AREI) provides a possible entry point at the regional and national levels. The EU and China should build on their existing pledges of support for AREI and jointly explore with African partners the development of pilot projects towards AREI's goal of installing at least 10 gigawatts (GW) of new and additional renewable energy generation capacity by 2020 and establishing the Africa Renewable Energy Institute. The single largest pledge in support of AREI by an EU member state has been made by Germany, which is well positioned to spearhead the proposed trilateral cooperation by building on its technical expertise and its G20 Presidency objective to support Africa's development, including in the area of renewable energy.
Keywords: 330; Governance; Klimawandel